Long-term vegetation change in the Succulent Karoo, South Africa following 67 years of rest from grazing - Rahlao, Sebataolo (FitzPatrick Institute of African Ornithology, 2025)
Changes in species richness and vegetation composition in the diverse semi arid Succulent Karoo vegetation of South Africa were investigated after 67 • (1937-2004) years of rest from grazing at the Worcester Veld Reserve. Vegetation change in 70 plots at this 75 ha site was assessed using multi variate ordination techniques. Changes in plant communities on termitaria sites were consistently greater than for adjacent off-termitaria sites and the north-facing slopes changed more than the south-facing slopes. There was a higher increase in diversity on off-termitaria than termitaria sites. On termitaria sites there was a general decrease in stem succulents, particularly Euphorbia mauretanica and an increase in long-lived evegreen shrubs such as Pteronia incana and Asparagus suaveo/ens. Most sites changed in a similar direction primarily determined by their association with termitaria and secondarily with .. aspect. These findings suggest a predictable and directional replacement sequence under changing disturbance (grazing) regimes in a semi-arid region